Analysis Of Service Quality Factors On Patient Satisfaction In The Pediatric Department Rsi At-Tin Husada Purbalingga - Oliviany, Windy; Kadarisman, Sumeidi; Utoyo, Widjajanti (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The quality of health services reflects the performance of health workers and affects community satisfaction. This study evaluates the impact of service quality on patient satisfaction at the RSI At-Tin Husada Purbalingga Children's Polyclinic. A quantitative approach using multiple linear regression analysis, examines five key service quality aspects: reliability, assurance, responsiveness, empathy, and physical evidence. Data were collected via a survey of 68 child patient companions, utilizing a tested questionnaire. Results indicate that the assurance dimension most significantly influences patient satisfaction, followed by empathy and reliability, all rated very good. While responsiveness and physical evidence also affect satisfaction, their influence is smaller. The study emphasizes the importance of a personalized approach and the need for improved facilities. Enhancing service quality across the five SERVQUAL dimensions can improve patient satisfaction, particularly in empathy and reliability. Key improvement areas include service timeliness, hospital reputation, complaint responsiveness, personalized care, standardization, and overall comfort. Recommendations include optimizing scheduling, strengthening public communication, implementing a responsive complaint system, enhancing patient recognition through training, adhering to uniform standards, and redesigning waiting areas for comfort. These insights support ongoing improvements in pediatric outpatient services and affirm the relevance of SERVQUAL in healthcare.